Teachers’ Strategies in Building Students’ English Learning Motivation - Harahap, Saima Putri; Siregar, Fitri Rayani; Rambe, Shokira Linda Vinde (English Education : English Journal for Teaching and Learning, 2023)
This research investigated the teachers’ strategy in building students’ English learning motivation. This research used qualitative research in descriptive method. The data sources of thie research were the two English teachers of the XI grade students of SMA N 4 Padangsidimpuan. The data were collected through observation and interview. This research is analyzed by using Miles and Huberman’s interactive model of data including reducing the data, diaplaying the data, taking conclusion and verification. This research used method triangulation to check the data trustworthiness. Based on the result of the research, it can be concluded that the strategies used by the English teachers were categorized into four part including creating the basic motivational ondition, generating intial motivation, maintaining and protecting motivation, and encouraging positive self-evaluation.